Characteristics and in Hospital Clinical Outcome of Patients with Non St-Segment Elevation Myocardial Infarction with Chronic Kidney Disease (Cardiovascular Journal, 2013)
Background: Nearly 40% of patients presenting with Non ST-Segment Elevation Myocardial Infarction (NSTEMI) have Chronic Kidney Disease (CKD). CKD is a powerful predictor of adverse events among NSTEMI patients. The purpose of the present study was to evaluate the in-hospital outcome of patients with Chronic Kidney Disease presenting with Non ST-Segment Elevation Myocardial Infarction. Methods: In this prospective observational study a total of 128 patients with NSTEMI were enrolled. They were divided equally in group I (NSTEMI with CKD) and group II (NSTEMI with normal renal function) on the basis of estimated glomerular filtration rate. Patients were considered to have CKD if he/she had documented history of CKD or estimated glomerular filtration rate